1999
DOI: 10.1203/00006450-199905010-00006
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Breast Feeding on Lymphocyte Subpopulations in Healthy Term Infants at 6 Months of Age

Abstract: Breast milk contains many immunologically active components that influence the development of the immune system of the breast-fed infant. The purpose of this study was to investigate the difference in specific lymphocyte subsets between breast-fed and formula-fed 6-mo-old infants. Peripheral blood samples were collected from 79 breast-fed (< 120 mL formula/wk) and 69 formula-fed (breast-fed < 4 wk) infants at 6 mo. All infants had been born at term and had no known illness at the time of blood collection. Pack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
49
5
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 10 publications
8
49
5
3
Order By: Relevance
“…A great number of natural-killer cells, suggesting a more mature immune system, have been found in breastfed infants than in formula-fed infants [27]. In addition, the pH level (hydrogen ion concentration, which can activate pepsin and promote protein digestion and absorption) in the stomach of breastfed children is better for the promotion of the protein-lipid α-lactalbumin, which induces apoptosis like death of tumor cells [28,29]. Infant formulas cannot mimic the array of protective properties of breast milk, which fits the infant owing to the dyadic connection between a mother and her baby.…”
Section: Discussionmentioning
confidence: 99%
“…A great number of natural-killer cells, suggesting a more mature immune system, have been found in breastfed infants than in formula-fed infants [27]. In addition, the pH level (hydrogen ion concentration, which can activate pepsin and promote protein digestion and absorption) in the stomach of breastfed children is better for the promotion of the protein-lipid α-lactalbumin, which induces apoptosis like death of tumor cells [28,29]. Infant formulas cannot mimic the array of protective properties of breast milk, which fits the infant owing to the dyadic connection between a mother and her baby.…”
Section: Discussionmentioning
confidence: 99%
“…However, some recent studies have shown that immunophenotypic differences in lymphocyte populations occur following exposure to maternal milk. These differences include a decrease in CD4+:CD8+ cells, an increase in interferon-γ levels and a greater number of natural killer cells (Pabst et al 1997;Hawkes et al 1999), and are consistent with age-related changes, suggesting that maternal milk can influence the maturation of the neonatal immune system (Hawkes et al 1999). The mechanism whereby maternal milk may induce these effects is not known.…”
Section: Maternal Milk and Immune Modulationmentioning
confidence: 99%
“…Infants who are breastfed exclusively for 6 months have a more developed immune system than those who are not exclusively breastfed. 40,41 Breastfeeding has also been shown to reduce the risks of the infant developing asthma and allergies 42 as well as childhood leukemia. 43 Cardiovascular disease risk is also reduced through the reduction of obesity, blood pressure, and cholesterol.…”
Section: Discussionmentioning
confidence: 99%